Stress-Related Growth in Adolescents Returning to School After COVID-19 School Closure - Waters, PhD, Lea; Allen, Kelly-Ann; Arslan, Gökmen (Frontiers in Psychology, 2021)
The move to remote learning during COVID-19 has impacted billions of students. While research shows that school closure, and the pandemic more generally, has led to student distress, the possibility that these disruptions can also prompt growth in is a worthwhile question to investigate. The current study examined stress-related growth in a sample of students returning to campus after a period of COVID-19 remote learning (n = 404, age = 13–18). The degree to which wellbeing skills were taught at school (i.e., positive education) before the COVID-19 outbreak and student levels of stress-related growth upon returning to campus was tested via structural equation modeling. Positive reappraisal, emotional processing, and strengths use in students were examined as mediators. The model provided a good fit (χ2 = 5.37, df = 3, p = .146, RMSEA = .044 [90% CI = .00–.10], SRMR = .012, CFI = 99, TLI = .99) with 56% of the variance in stress-related growth explained. Positive education explained 15% of the variance in cognitive reappraisal, 7% in emotional processing, and 16% in student strengths use during remote learning. The results are discussed using a positive education paradigm with implications for teaching wellbeing skills at school to foster growth through adversity and assist in times of crisis.